Prospective evaluation of preoperative lung ultrasound for prediction of perioperative outcome and myocardial injury in adult patients undergoing vascular surgery (LUPPO study) - Gillmann, Hans-Jörg; Dieding, Jasmin; Schrimpf, Claudia; Janßen, Henrike; Sahlmann, Bianca; Rustum, Saad; Aper, Thomas; Lichtinghagen, Ralf; Teebken, Omke E.; Theilmeier, Gregor; Larmann, Jan (Minerva Anestesiologica, 2020)
Europe PMC is an archive of life sciences journal literature., Prospective evaluation of preoperative lung ultrasound for prediction of perioperative outcome and myocardial injury in adult patients undergoing vascular surgery (LUPPO study).